2019
DOI: 10.3389/fimmu.2019.01946
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to Human Herpesviruses in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome Patients

Abstract: Myalgic encephalomyelitis, also referred to as chronic fatigue syndrome (ME/CFS) is a debilitating disease characterized by myalgia and a sometimes severe limitation of physical activity and cognition. It is exacerbated by physical and mental activity. Its cause is unknown, but frequently starts with an infection. The eliciting infection (commonly infectious mononucleosis or an upper respiratory infection) can be more or less well diagnosed. Among the human herpesviruses (HHV-1-8), HHV-4 (Epstein-Barr virus; E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 72 publications
8
36
0
1
Order By: Relevance
“…In a further global screening of serum antibody responses to an EBV peptide array, the same authors in serum of patients with ME/CFS revealed quite similar EBV IgG antibody response pattern as in sera of healthy controls except for the significantly enhanced IgG responses to several EBNA‐6 peptides 25 . On the contrary, according to a recent study, no increased EBV‐CA IgG reactivity over EBNA‐1 in ME/CFS cohorts is found and EBNA‐6 peptide IgG reactivity is not significantly different between the ME/CFS and healthy control samples 27 . In addition, some earlier studies also reported no differences in IgG titers against EBV‐CA, EBNA‐1 and EA 10,26,31 .…”
Section: Discussionmentioning
confidence: 53%
“…In a further global screening of serum antibody responses to an EBV peptide array, the same authors in serum of patients with ME/CFS revealed quite similar EBV IgG antibody response pattern as in sera of healthy controls except for the significantly enhanced IgG responses to several EBNA‐6 peptides 25 . On the contrary, according to a recent study, no increased EBV‐CA IgG reactivity over EBNA‐1 in ME/CFS cohorts is found and EBNA‐6 peptide IgG reactivity is not significantly different between the ME/CFS and healthy control samples 27 . In addition, some earlier studies also reported no differences in IgG titers against EBV‐CA, EBNA‐1 and EA 10,26,31 .…”
Section: Discussionmentioning
confidence: 53%
“…Specific changes in the proteome of CSF of ME/CFS patients involved the accumulation of complement components, which signify antibody activity (19). In a recent publication from our group, the serological profile of the same ME/CFS patient cohorts demonstrated evidence of minor alterations of antibody reactivities against the ubiquitous herpesviruses when compared to healthy controls (20). These alterations may indicate shortcomings in humoral responses in ME/CFS which are hallmarks of autoimmune diseases.…”
Section: Introductionmentioning
confidence: 78%
“…Blomberg et al (22) used a suspension multiplex immunoassay to detect antibodies against various herpesviruses' antigens, derived from proteins expressed during latency or late lytic replication (Figure 1), with the goal of determining differences in antibody titers against these antigens between ME/CFS patients and controls. However, no rationale was given as to why these particular antigens were chosen and what association, if any, they may have with ME/CFS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ability of a virus protein to generate an antibody response is dependent upon the amount of protein present in the host and its antigenicity. It is also not clear why Blomberg et al (22) included HSV-1/2, human cytomegalovirus, HHV-7, and varicella zoster virus (VZV) in their study since there are no up-to-date literature reports establishing a serological relationship between these viruses and ME/CFS. Along these lines, measuring the response in patients' sera using purified virus lysate would only detect antibodies to proteins that are components of the virion (capsid proteins, glycoproteins, and tegument proteins) but not proteins expressed during virus lytic/abortive-lytic replication (Figure 1).…”
Section: Discussionmentioning
confidence: 99%